2017
DOI: 10.1016/j.apenergy.2017.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Industrial excess heat for district heating in Denmark

Abstract: Excess heat is available from various sources and its utilisation could reduce the primary energy use. The accessibility of this heat is however dependent amongst others on the source and sink temperature, amount and potential users in its vicinity. In this work a new method is developed which analyses excess heat sources from the industrial sector and how they could be used for district heating. This method first allocates excess heat to single production units by introducing and validating a new approach. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(52 citation statements)
references
References 20 publications
2
47
0
Order By: Relevance
“…11 The potential for increased usage of industrial excess heat in different countries, regions, or industrial sectors has been investigated in many studies. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Most focus primarily on the potential usage of excess heat for district heating. 12,[14][15][16]18,19,25 Other opportunities for utilizing industrial excess heat include delivery to other industrial plants, electricity production in combined heat and power (CHP) plants, and low temperature applications such as greenhouses and fish farming.…”
Section: Introductionmentioning
confidence: 99%
“…11 The potential for increased usage of industrial excess heat in different countries, regions, or industrial sectors has been investigated in many studies. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Most focus primarily on the potential usage of excess heat for district heating. 12,[14][15][16]18,19,25 Other opportunities for utilizing industrial excess heat include delivery to other industrial plants, electricity production in combined heat and power (CHP) plants, and low temperature applications such as greenhouses and fish farming.…”
Section: Introductionmentioning
confidence: 99%
“…Bühler et al 19 state, for example, that "the use of actual energy use data or excess heat amounts obtained from site-specific analyses has the highest accuracy" for assigning excess heat amounts to a given production unit. Bühler et al 19 state, for example, that "the use of actual energy use data or excess heat amounts obtained from site-specific analyses has the highest accuracy" for assigning excess heat amounts to a given production unit.…”
Section: Novelty Statementmentioning
confidence: 99%
“…13 The advantage of such methods is that they are based on data that are relatively simple to obtain. Bühler et al 19 also relied on thermal process-related CO 2 emissions to allocate excess heat estimations for different industrial subsectors to individual production sites. The bottom-up approach originally suggested by McKenna and Norman 13 and further developed by Hammond and Norman 16 has been adopted in several more recent studies such as the work of Miró et al 17 Papapetrou et al 18 extended and updated the approach by adjusting the conversion factors suggested by Hammond and Norman 16 for the UK for the period 2000 to 2003 in order to be applicable for other EU countries in 2015.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bühler et al [6][7][8] have conducted economic analyses of the possibilities to use industrial excess heat from thermal processes for district heating. They considered spatiotemporal aspects and ensured the economic feasibility by comparisons to alternative heat sources for the DH network and to energy-efficiency measures, which would decrease the availability of industrial excess heat.…”
Section: Introductionmentioning
confidence: 99%